Meliaceae endémicas del Perú - León, Blanca (2006)
The Meliaceae are represented in Peru by ten genera and 75 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all trees. Here we recognize three endemic species in the same number of genera. These endemic species are found in areas of Humid Lowland Amazonian Forests, Mesoandean and Dry Forests regions, between 100 and 1700 m elevation. No endemic Meliaceae have been registered today within Peru’s protected areas system.